Tinjauan Yuridis Terhadap Tindak Pidana PembunuhanOleh Anggota Kopassus - Marmiati, Dina; , Sudaryon, S.H., M.Hum (2017)
This research aims to know the legislation about crimes of the criminal acts of murder committed by members of the Indonesian special forces, as well as to know law enforcement crime murder committed by members of kopassus. The method of the approach that the author shared juridical normative approach is. The type of research used in this study the author is using this type of descriptive research. Method of data collection in this research study using the technique of librarianship. Based on the results of the research and the discussion then it can be inferred that the rule of law regarding criminal acts of murder committed by members of Kopassus is regulated in the provisions of the book of the law of criminal law (PENAL CODE) and the book of the law of military criminal law (MCL). Law enforcement against the defendant in addition to incur criminal, in the form of imprisonment, are also subject to additional criminal, namely in the form of dismissal from military service.